Contractualisation of family law: Is it possible in Turkey? - Kapancı, Kadir Berk (Vedat Kitapçılık, 2015)
Contractual freedom and private autonomy are the basic principles of Turkishprivate law. However, such statement may not apply in the field of familylaw. Contrary to the general assumption in Turkish private law, contractualfreedom and private autonomy are not the default rules in Turkish familylaw system.
Keywords: Turkish Reports; International Congress